On the Controllability of Conformable Fractional Deterministic Control Systems in Finite Dimensional Spaces. (10th March 2020) - Jneid, Maher; Awadalla, Muath
Abstract : In this paper, we establish a set of convenient conditions of controllability for semilinear fractional finite dimensional control systems involving conformable fractional derivative. Indeed, sufficient conditions of controllability for a semilinear conformable fractional system are presented, assuming that the corresponding linear systems are controllable. The present method is based on conformable fractional exponential matrix, Gramian matrix, and the iterative technique. Two illustrated examples are carried out to establish the facility and efficiency of this technique.